All you need is law: Italian courts break new ground in the treatment of same-sex marriage. (1st January 2014) - Fichera, Massimo; Hartnell, Helen
On 15 March 2012 the Italian Corte di Cassazione delivered a judgment in case 4184/12 which marks a fundamental change of direction in the treatment of same-sex marriage in the Italian legal system. This case must be read in conjunction with other recent cases decided by Italian and European courts, which are relied upon by the Corte di Cassazione. In fact, a short outline of the case-law illustrates both the piecemeal nature of legal developments affecting same-sex marriage and the complex mix of issues that arise in this legal field. The issue of same-sex marriage bridges private and public law, and implicates family, free movement, and equality (non-discrimination) rights under national and European provisions. This paper argues that, even if the Court's ruling did not confer upon same-sex couples a specific right to marry or to have a marriage registered in Italy, it still extended their status by recognising a right to family life and, on that basis, a right to be treated on an equal footing with heterosexual married couples.